Granular media : between fluid and solid - Andreotti, Bruno; Forterre, Yoël, 1973-; Pouliquen, Olivier (Cambridge University Press, 2013)
"Sand, rice, sugar, snow, cement . . . Although ubiquitous in our daily lives, granular media still challenge engineers and fascinate researchers. This book provides the state of the art of the physics of granular media and recent advances in the field. The book presents the fundamental properties of granular materials: interactions between grains; solid, liquid and gaseous behaviours; coupling with a fluid; and sediment transport and formation of geological structures. Descriptions of the phenomena combine qualitative and formal arguments, coming from areas as diverse as elasticity, plasticity, statistical physics, fluid mechanics and geomorphology. Many examples of the astonishing behaviours of granular media are presented, icluding avalanches, segregation, dune song and quicksand. This book is ideal for graduate students and researchers in physics, applied mathematics and engineering"--Vydavatelská anotace